2022
DOI: 10.9734/jpri/2022/v34i2b35375
|View full text |Cite
|
Sign up to set email alerts
|

Case Report on Bipolar Affecting Disorder with Hypertension

Abstract: Introduction: Bipolar disorder (BD) is one of the foremost frequent chronic disorders in populations where depression is usually present; however, in chronic cases, it can raise the danger of death. Bipolar major Affective Disorder (BPAD) may be a common and recurrent psychiatric disorder that affects people everywhere on the planet. Tt's characterized by episodes of mania, hypomania, hyperactivity, and depression. Findings of Clinical: A 45-year-old woman from Chandrapur is admitted to the (AVBRH) Archa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Studies have shown that hypertensive patients often exhibit cardiovascular dysfunction and vascular tension, which can potentially influence blood circulation as well as the absorption, distribution, and elimination of medications. Common comorbid factors in hypertensive and manic patients may also interact with each other (Deotale et al, 2022;Gimenez-Palomo et al, 2022). For instance, cardiovascular diseases, metabolic syndrome, and obesity, closely associated with hypertension, may be more prevalent among individuals with mania.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%
“…Studies have shown that hypertensive patients often exhibit cardiovascular dysfunction and vascular tension, which can potentially influence blood circulation as well as the absorption, distribution, and elimination of medications. Common comorbid factors in hypertensive and manic patients may also interact with each other (Deotale et al, 2022;Gimenez-Palomo et al, 2022). For instance, cardiovascular diseases, metabolic syndrome, and obesity, closely associated with hypertension, may be more prevalent among individuals with mania.…”
Section: O N L I N E F I R S T a R T I C L Ementioning
confidence: 99%